Column readout circuit with improved offset mismatch and charge sharing for CMOS image sensor. (December 2019) - Guo, Zhongjie; Yu, Ningmei; Wu, Longsheng
Abstract: High linearity and low noise column readout chain are two key factors in CMOS image sensor. However, offset mismatch and charge sharing always exist in the conventional column wise readout implementation, even adopting the technology of correlated double sample. A simple column readout circuit with improved offset mismatch and charge sharing for CMOS image sensor is proposed in this paper. Based on the bottom plate sampling and fixed common level method, this novel design can avoid the offset nonuniformity between the two buffers. Also, the single buffer and switched capacitor technique can effectively suppress the charge sharing caused by the varied operating point. The proposed approach is experimentally verified in a 1024 × 1024 prototype chip designed and fabricated in 55 nm low power CMOS process. The measurement results show that the linear range is extended by 20%, the readout noise of bright and dark fields is reduced by 40% and 30% respectively, and the improved photo response nonuniformity is up to 1.16%. Finally, a raw sample image taken by the prototype sensor shows the excellent practical performance.